Stress Management Training to Reduce Academic Distress and Increase Self-Efficacy in Students Memorizing the Quran - Wafa, Sirril; Hartini, Nurul; Cahyanti, Ika Yuniar (Faculty of Psychology, Universitas Gadjah Mada, 2025)
The study aimed to test the effectiveness of stress management training in reducing academic distress and increasing self-efficacy. The research used a quasi-experimental pretest-posttest control group design. It involved 10 mahasantri or university students who memorized the Quran and experienced a high level of academic stress and low self-efficacy. The stress management training lasted for seven sessions. The research employed the academic stress scale and general self-efficacy scale to collect data from the participants. Data analysis was conducted using an independent sample t-test based on the gain score. The results showed that stress management training was effective in reducing academic distress and increasing self-efficacy, with a relatively large effectiveness value. The results imply that low academic stress and high self-efficacy improve the chance of students completing their education and memorizing the Quran.